Algerian secret radio as a model) The experience of distance learning at the Algerian University - Sallemine, hanya; boudjema, amara (Journal of Social Sciences and Humanities, 2023)
Our study aims to explore the distance learning experience at Mohamed Boudiaf University in M'sila, as it is one of the leading experiences, compared to the experiences of other Algerian universities, and to try to explore the evolution of the stages of the experiment, in addition to highlighting the most important strengths and weaknesses of the experience, the extent to which the Moodle University of M'sila platform is used, and the most important statistics and figures As well as the future prospects to be applied in distance education at the university. The field study was based on the descriptive approach, using the interview tool, and the results of the field study concluded that the experiment is a pioneering experiment, despite the difficulties and obstacles, going towards the digitization of the university, and thus the actual establishment of distance education.